Genes associated with polymorphic variants predicting lung function are differentially expressed during human lung development. Issue 1 (December 2016) - Miller, S.; Melén, E.; Merid, S.; Hall, I.; Sayers, I.
Abstract Background Recent meta-analyses of genome-wide association studies have identified single nucleotide polymorphisms (SNPs) within/near 54 genes associated with lung function measures. Current understanding of the contribution of these genes to human lung development is limited. We set out to further define i) the expression profile of these genes during human lung development using a unique set of resources to examine both mRNA and protein expression and ii) the link between key polymorphisms and genes using expression quantitative trait loci (eQTL) approaches. Methods The mRNA expression profile of lung function associated genes across pseudoglandular and canalicular stages of lung development were determined using expression array data of 38 human fetal lungs. eQTLs were investigated for selected genes using blood cell and lung tissue data. Immunohistochemistry of the top 5 candidates was performed in a panel of 24 fetal lung samples. Results Twenty-nine lung function associated genes were differentially expressed during lung development at the mRNA level. The greatest magnitude of effect was observed for 5 genes;TMEM163, FAM13A andHHIP which had increasing expression andCDC123 andPTCH1 with decreased expression across developmental stages. Focussed eQTL analyses investigating SNPs in these five loci identified several cis-eQTL's. Protein expression of TMEM163 increased and CDC123 decreased with fetal lung age in agreement with mRNA data. Protein expression in FAM13A, HHIP and PTCH1 remained relatively constant throughout lung development. Conclusions We have identified that > 50 % of lung function associated genes show evidence of differential expression during lung development and we show that in particular TMEM163 and CDC123 are differentially expressed at both the mRNA and protein levels. Our data provides a systematic evaluation of lung function associated genes in this context and offers some insight into the potential role of several of these genes in contributing to human lung development.